Vocabulary knowledge Among English Majors in a Saudi Arabia University - Alharbi, Jamilah Maflah (Technium Social Sciences Journal, 2021)
One of the main challenges that learners may encounter in learning a foreign language is vocabulary. Vocabulary is defined as a mandatory part of language use because lack of vocabulary knowledge (VK) for learners has led to difficulties in the process of learning such language. This study sets out to assess the receptive and productive VK of first-year English major students. The researcher conducted the study on 65 students from Majmaah University who were made up of first-year English major students. The instruments used in the study were the Receptive Vocabulary Levels Test (VLT) by Nation and Schmitt et al. (2001) and the Productive VLT by Nation & Laufer (1999) The VLTs were used to assess the participants’ receptive and productive VK respectively. The findings of this study reveal that the productive VK of male students is significantly lower at the 3,000 word level compared to the 1,000 word level. This study fills the gap of knowledge regarding gender differences in acquiring receptive and productive vocabulary among Saudi EFL learners.